Augmented Reality in Geography Education: Developing Innovative Digital Modules on Indonesia’s Cultural Diversity - Baihaqi Ghazian Zul'hilmi; Ibipo Johnston-Anumonwo (Future Space: Studies in Geo-Education, 2025)
The need for learning modules in the 21st century leads to the use of technology, digital media, and information. The fact is that learning resources in schools using printed books are conventional and contain only knowledge information. The purpose of this research was conducted to produce a digital teaching module assisted by AR (Augmented Reality) on the material of cultural diversity in Indonesia. The development of this digital teaching module was carried out with the ADDI model with this research only up to the development stage. The feasibility of the digital teaching modules was assessed through validation by media, language, and material experts. The subject of the feasibility of digital teaching modules is students of class XI IPS 1 MA Bilingual Batu. The validation results showed an 87% feasibility level, while the student understanding test results ranged from 76-85%, with 53% of students demonstrating high comprehension. These results suggest that the digital module effectively enhances students' understanding of cultural diversity, and could be utilized to support similar learning contexts in other educational settings.